PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS XI IPA4 SMA NEGERI 5 PEKANBARU - Shinta Purnama Sari; Sakur Sakur; Jalinus Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research is a class action research that aims to increase the outcomes of mathematics learning of students by applying Problem Based Learning (PBL). The subjects of this research are the student of class XI IPA4 SMA Negeri 5 Pekanbaru at second semester of academic years 2018/2019 which total number of participant are 36 students, consists of 16 male students and 20 female students with heterogeneous academic achievement. The data needed is data on teacher and student activities collected by observation techniques and analyzed by descriptive narrative and data on student learning outcomes collected by test techniques and analyzed with descriptive statistics. Weaknesses in cycle I are improved in the implementation of cycle II in accordance with the improvement plan. The results of the study showed that the implementation of the learning process in cycle II was improved from cycle I. The result of this research could be concluded that the implementation of Problem Based Learning model can increase the outcomes of mathematics learning of students of grade XI Science4 SMA Negeri 5 Pekanbaru on the second semester academic years 2018/2019 on matrix.Key Words : The outcomes of mathematics learning, Problem Based Learning, class action research